A Classification of Fourth-Order Dissipative Differential Operators - Tao Wang; Ji-jun Ao; Mei-chun Yang (Journal of Function Spaces)
This paper is devoted to the classification of the fourth-order dissipative differential operators by the boundary conditions. Subject to certain conditions, we determine some nonself-adjoint boundary conditions that generate the fourth-order differential operators to be dissipative. And under certain conditions, we prove that these dissipative operators have no real eigenvalues.